SRSF1 Deficiency Impairs the Late Thymocyte Maturation and the CD8 Single-Positive Lineage Fate Decision - Ji, Ce; Bao, Li; Yuan, Shunzong; Qi, Zhihong; Wang, Fang; You, Menghao; Yu, Guotao; Liu, Jingjing; Cui, Xiao; Wang, Zhao; Liu, Juanjuan; Guo, Wenhui; et al. (Frontiers in Immunology, 2022)
The underlying mechanisms of thymocyte development and lineage determination remain incompletely understood, and the emerging evidences demonstrated that RNA binding proteins (RBPs) are deeply involved in governing T cell fate in thymus. Serine/arginine-rich splicing factor 1 (SRSF1), as a classical splicing factor, is a pivotal RBP for gene expression in various biological processes. Our recent study demonstrated that SRSF1 plays essential roles in the development of late thymocytes by modulating the T cell regulatory gene networks post-transcriptionally, which are critical in response to type I interferon signaling for supporting thymocyte maturation. Here, we report SRSF1 also contributes to the determination of the CD8+ T cell fate. By specific ablation of SRSF1 in CD4+CD8+ double positive (DP) thymocytes, we found that SRSF1 deficiency impaired the maturation of late thymocytes and diminished the output of both CD4+ and CD8+ single positive T cells. Interestingly, the ratio of mature CD4+ to CD8+ cells was notably altered and more severe defects were exhibited in CD8+ lineage than those in CD4+ lineage, reflecting the specific function of SRSF1 in CD8+ T cell fate decision. Mechanistically, SRSF1-deficient cells downregulate their expression of Runx3, which is a crucial transcriptional regulator in sustaining CD8+ single positive (SP) thymocyte development and lineage choice. Moreover, forced expression of Runx3 partially rectified the defects in SRSF1-deficient CD8+ thymocyte maturation. Thus, our data uncovered the previous unknown role of SRSF1 in establishment of CD8+ cell identity.